Environmetal education: prÃxis educative in the consciousness of the problematic during - Clesley Maria Tavares do Nascimento (2006)
The basic reflection of this work isnât restricted to waste selective recollection itself, but it is mainly linked to the educational aspect of it, putting it into context at the scholar environment and in the present day industrial capitalist society. Thus, a case study was carried out at ClÃvis BevilÃqua state school aiming to analyze a selective recollection project developed there, identifying the chief challenges and solutions found by its collaborators and whether that experience contributes to build a new paradigm before the problem of solid waste. We aimed to identify, during discussions about waste selective recollection, the way how we can build an environmental educational process concerned to solid waste at the core of scholar institutions. We chose the dialectical method to guide the inquiring look of the study, build a reflexive bridge between the capitalist productive system and the solid waste productive chain, revealing the dialectical nature of the considered social relations. The field work showed that the waste selective recollection trespasses the condition of simple recycling step, having a conscious and effective educational potential. If that recollection is developed under dialectical perspective, it contributes to develop a new position in relation to waste problems, not only attitudinal but social. Thus, it should be developed in all educational institutions.